Penerapan Senam Ergonomik Untuk Mengurangi Nyeri Sendi Pada Keluarga Dengan Gout Arthritis - Putri Nur Padilah; Hidayat Turochman (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Background Gouty arthritis can be treated non-pharmacologically. Nonpharmacological treatment that can be done is ergonomic gymnastics is a gymnastic movement that is done to reduce pain in gout sufferers. The purpose of the study was to gain real experience in applying ergonomic exercises to families with Gouty Arthritis. The research method used is descriptive method with a case study approach by taking one case in the family by providing ergonomic exercise interventions and providing nursing care. The results of the study, after the application of ergonomic gymnastics for 3 days 1x / day with 5 minutes, Mrs. R's family, especially Mrs. R with gout decreased, initially 6.7 mg / dl with a pain scale of 5 down to 5 mg / dl with a pain scale of 0 (not felt anymore). The conclusion of the application of ergonomic gymnastics in families with gouty arthritis is well implemented, namely increased family knowledge about gout and a decrease in uric acid levels and pain scale from 6.7 mg / dl pain scale 5 to 5 mg / dl with pain scale 0, and the family can take care of family members who experience gout.